2015
DOI: 10.1111/ane.12475
|View full text |Cite
|
Sign up to set email alerts
|

Anti-JC virus seroprevalence in a Finnish MS cohort

Abstract: The study confirmed a high anti-JCV antibody prevalence in patients with MS and its association with age and male gender but not with disease-modifying therapies. Our data suggest that therapy with natalizumab may cause a decrease in anti-JCV antibody levels, suggesting an immunosuppressive effect of natalizumab without an impact on JCV seroprevalence. The results of studies performed until now confirm the predictive value of anti-JCV antibody measurement in the assessment of PML risk; however, changes in sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 38 publications
7
23
2
Order By: Relevance
“…The latter is according to earlier data that have been published in our centre, although other literature did not show this association . In a recent publication of a Finnish cohort of patients with MS, it was also suggested that natalizumab might have a decreasing effect on the anti‐JCV antibody levels …”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The latter is according to earlier data that have been published in our centre, although other literature did not show this association . In a recent publication of a Finnish cohort of patients with MS, it was also suggested that natalizumab might have a decreasing effect on the anti‐JCV antibody levels …”
Section: Discussionsupporting
confidence: 75%
“…The risk of seropositivity rises with increasing age and male gender . But several reports show that the annualized seroconversion rate in natalizumab‐treated patients with MS seems to be higher than expected, possibly due to a higher sensitivity caused by natalizumab usage …”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Egli et al [8] reported a prevalence of anti-JCV antibody in 58% of 400 healthy subjects (age 20–29 years) and 68% in older cases (50–59 years), which is in accordance with an Australian study finding [10]. In a Finnish study included in this systematic review, longer disease duration was not correlated with JCV seroprevalence, while they found that higher age and male gender were related to higher seroprevalence [15].…”
Section: Discussionsupporting
confidence: 73%
“…However, there has been no reduction in the NTZassociated PML incidence concomitant with the utilization of JCPyV serology (Cutter and Stuve 2014), and thus it seems insufficient to evaluate complete risk. Moreover, as 60-70% of the MS patients are JCPyV Ab positive, further tools are needed to narrow down high PML risk among patients receiving NTZ (Kolasa et al 2016;Olsson et al 2013). Previously evaluated tools based on leukocyte cell membrane markers such as CD11a, CD49d, and CD62L (Basnyat et al 2015;Jilek et al 2013;Schwab et al 2013), and quantification of JCPyV load in the blood or urine still lack applicability in a clinical setting (Chen et al 2009;Jilek et al 2010;Rudick et al 2010).…”
Section: Introductionmentioning
confidence: 99%